Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Klinik Pratama Shinta Medika Pekanbaru - Asmita, Nila (Journal of Economic, Management, Business, Accounting Sustainability, 2024)
This research aims to determine and analyze the influence of service quality on patient satisfaction at the Pratama Shinta Medika Clinic. The analysis in this study uses the independent variable Service Quality while the dependent variable is Patient Satisfaction. The sample for this study was patients who visited the Pratama Shinta Medika Clinic Pekanbaru. Sampling was carried out using the Accidental Sampling method. The data collection technique was carried out by distributing questionnaires. The patient population of Pratama Shinta Medika Clinic is 2,786 people and the sample obtained was 97 patients. The Asymp.Sig (2-tailed) One-Simple Kolmogorov Smirnov Test result was 0.069, the value is above 0.05 and it can be concluded that the data is normally distributed. Service Quality with a calculated t value of 2.466 and a t table value of 1.985 so that t calculated > t table or 2.466 and a significant level of 0.000 < 0.05, which means that the Service Quality variable partially has a significant effect on patient satisfaction. The adjusted R square value is 0.050. This shows that the percentage contribution of the dependent variable (Service Quality) to the dependent variable (Patient Satisfaction) is 50.00%. Or the variation in the independent variable (Service Quality) used in the regression model is able to explain 50.00% of the variation in the dependent variable (Patient Satisfaction). Meanwhile, the remaining 50.00% is influenced or explained by other variables not included in this research. The constant is 8.987, which means that the variables Service Quality (X) and Patient Satisfaction (Y) have a value of 8.987. The regression coefficient for the Service Quality variable (X) has increased by 1%, so patient satisfaction (Y) will increase by 0.118 with a positive sign, which means that the higher the quality of service, the patient satisfaction (Y) will also increase. increase.